Fabrication and characterization of electrospun cellulose-reinforced polycaprolactone nanofibrous membrane filled with Moringa oleifera leaf powder - Pagaduan, James Nicolas M.
Polycaprolactone (PCL) is a synthetic biodegradable polymer that could be appropriate for applications that require stringent disposal procedures such as in extracellular matrix (ECM) device for wound healing. However, its hydrophobicity and inertness to bacteria limit its application. In this study, an electrospun membrane was prepared from the suspension of hydrophilic, mechanically reinforcing cellulose particles and anti-bacterial, hemostatic Moringa oleifera leaf powder (MOLP) in PCL. Subjecting the membrane to MTT [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide] assay revealed that the electrospun nanofibers were non-cytotoxic. Based on thermogravimetric analysis, heat sterilization treatment should not adversely affect the structural integrity of the membranes since the peak of first degradation event occurred at 315°C, which is much lower than the typical sterilization condition. Mechanical testing indicated that the fabricated materials (0.40 mm thick) had ultimate tensile strength of 0.229-0.230 MPa and maximum strain of 32.65 - 55.54% which can match the typical values for commercial wound dressings (at least 1 mm) upon increase in thickness. However, analysis had shown that adding cellulose into the structure did not result to the desired effect of increasing the tensile strength. In fact, it reduced the strength by 47%, and thus was removed in the preparation of subsequent membranes. It also did not enhance the hydrophilicity of the nanofibrous membrane. Addition of 10 percent w/v MOLP increased the water affinity, as demonstrated by the reduction in time for complete wetting of the membrane by water from 32.33 to 2.78 min. It also improved the hemostatic potential marked by the decrease in blood clotting index after 30 min from 81.7 to 40.0, and imparted anti-bacterial activity against E. coli (no growth underneath the membrane) and S. aureus (inhibition zone diameter of 7.5 mm). FESEM micrographs showed membrane morphologies similar to ECM that is comprised of fibers with diameters ranging from 60 700 nm and fiber beads which are typical manifestations of its resistance to stretching or formation of fibers. Full factorial 2k design of experiment was employed to determine the effect of suspension and spinning parameters on fiber diameter wherein smaller diameter corresponds to a more porous structure of the membrane, which is desirable for an ECM device. MOLP concentration and spinning distance did not have significant effect while a decrease in PCL concentration and an increase in applied voltage led to a reduction in fiber diameter from 481.7 to 105.7 nm and from 340.0 to 247.4 nm, respectively. Overall, this work showed the successful fabrication of an electrospun membrane suitable for potential use as an ECM wound healing device by exploiting the antimicrobial and hemostatic properties of the locally available herbal plant Moringa oleifera.